Pengaruh Media Audiovisual Terhadap Pengetahuan dan Sikap Ibu Hamil dalam Mengkonsumsi Tablet Tambah Darah di Puskesmas Putri Ayu Kota Jambi - Rosmaria Rosmaria (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
The problem that often occurs in pregnancy is malnutrition in pregnant women. One of the effects of malnutrition is anemia and KEK (Chronic Energy Deficiency). In 2018 anemia in Putri Ayu Health Center was 18%. From the initial survey that has been done, there are 7 out of 10 pregnant women who show that they do not know the correct way to take blood-added tablets. The purpose of this study was to determine the effect of audiovisual media on the knowledge and attitudes of pregnant women in consuming blood-added tablets. This research is a type of quantitative research with a quasi-experimental design. This research design uses a pre and post-test one group design. The population of this study was 235 pregnant women in the second trimester who had their pregnancy checked at the Putri Ayu Health Center, Jambi City. The sample was taken using purposive sampling technique, the sample in this study was obtained as many as 52 samples. The results of the level of knowledge in this study, namely before being given audiovisual media in the form of videos to pregnant women, the average value (mean) was 8.42. Then after being given audiovisual media, the average value of mother's knowledge increased to 13.75. For the results of attitudes before being given audiovisual media, some respondents had a negative attitude. However, after being given audiovisual media, the attitude of pregnant women changed to be more positive. From the statistical test, it is known that there is an effect of audiovisual media on the knowledge and attitudes of pregnant women with p-value = 0.00 (p <0.05). The conclusion of this study is the influence of audiovisual media in the form of videos on the knowledge and attitudes of pregnant women in consuming blood-added tablets at the Putri Ayu Health Center, Jambi City 2021. It is hoped that this study can help the health centre to provide information to pregnant women to consume blood plus tablets properly